Fluorescent pH‐Responsive Probes Based on Water‐Soluble Boron‐Dipyrromethene (BODIPY) Derivatives, Featuring Long‐Wavelength Emission. Issue 43 (3rd July 2018) - Sutter, Alexandra; Elhabiri, Mourad; Ulrich, Gilles
Abstract: We describe here the synthesis of water‐soluble red/NIR‐emissive, boron‐dipyrromethene (BODIPY) derivatives displaying optical (absorption and emission) responses in pH range of 4–8. Substitution close to the tertiary aniline or the phenol subunits selected as the proton‐sensitive sites allowed us to finely tune the pH ranges. Furthermore, the introduction of sulfobetaine functions at the boron centre of these pH‐responsive BODIPYs afforded valuable fluorescent dyes in the red/NIR region in aqueous media, for which the steric hindrance and electrostatic repulsions prevent their non‐emissive aggregation. All the absorption and emission studies, as well as the protonation properties were investigated in aqueous, ethanolic and saline solutions (mimicking physiological conditions). Interestingly, the systems present a fluorescent ratiometric protonation response in EtOH, but the non‐protonated form is almost a non‐fluorescent species under quasi‐physiological conditions (saline aqueous solutions) due to the fading of the emissive character of the low‐lying charge‐transfer transition in the presence of a supporting electrolyte. Abstract : The red boron ! Fully water‐soluble, red‐emissive, pH‐responsive fluorescent boron‐dipyrromethene (BODIPY) derivatives have been synthesised and their optical properties investigated.